Surrogate Markers of Cardiovascular Risk and Chronic Obstructive Pulmonary Disease: A Large Case-Controlled Study. Issue 3 (March 2018) - Fisk, Marie; McEniery, Carmel M.; Gale, Nichola; Mäki-Petäjä, Kaisa; Forman, Julia R.; Munnery, Margaret; Woodcock-Smith, Jean; Cheriyan, Joseph; Mohan, Divya; Fuld, Jonathan; Tal-Singer, Ruth; Polkey, Michael I.; et al.
Abstract : Cardiovascular disease is a common comorbidity and cause of mortality in chronic obstructive pulmonary disease. A better understanding of mechanisms of cardiovascular risk in chronic obstructive pulmonary disease patients is needed to improve clinical outcomes. We hypothesized that such patients have increased arterial stiffness, wave reflections, and subclinical atherosclerosis compared with controls and that these findings would be independent of smoking status and other confounding factors. A total of 458 patients with a diagnosis of chronic obstructive pulmonary disease and 1657 controls (43% were current or ex-smokers) with no airflow limitation were matched for age, sex, and body mass index. All individuals underwent assessments of carotid–femoral (aortic) pulse wave velocity, augmentation index, and carotid intima–media thickness. The mean age of the cohort was 67±8 years and 58% were men. Patients with chronic obstructive pulmonary disease had increased aortic pulse wave velocity (9.95±2.54 versus 9.27±2.41 m/s; P <0.001), augmentation index (28±10% versus 25±10%; P <0.001), and carotid intima–media thickness (0.83±0.19 versus 0.74±0.14 mm; P <0.001) compared with controls. Chronic obstructive pulmonary disease was associated with increased levels of each vascular biomarker independently of physiological confounders, smoking, and other cardiovascular risk factors. In this large case-controlled study, chronic obstructive pulmonary disease was associated with increased arterial stiffness, wave reflections, and subclinical atherosclerosis, independently of traditional cardiovascular risk factors. These findings suggest that the cardiovascular burden observed in this condition may be mediated through these mechanisms and supports the concept that chronic obstructive pulmonary disease is an independent risk factor for cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.